2009
DOI: 10.1080/10837450802572367
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acid modifiedDioscoreastarches as direct compression excipient

Abstract: Starches obtained from four different Dioscorea species namely White (D. rotundata), Bitter (D. dumetorum), Chinese (D. oppositifolia) and Water yam (D. alata), were modified by acid hydrolysis and the physicochemical, material and tablet formation properties of the starches were investigated with the aim of determining their usefulness as a direct compression excipient in pharmaceutical tablets. The results obtained indicate that the physicochemical, material and tablet properties of the acid modified Dioscor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
5
24
0
Order By: Relevance
“…Recently, starches from four different Dioscorea species namely white (D. rotundata), bitter (D. dumetorum), Chinese (D. oppositifolia) and water yam (D. alata) have been modified by acid hydrolysis and the physicochemical, material and tablet formation properties of the starches have been investigated with the aim of determining their relative usefulness as a direct compression excipient in pharmaceutical tablets (Odeku and Picker-Freyer, 2009a). The results showed that the acid modified starches differed considerably in their physicocemical and material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, starches from four different Dioscorea species namely white (D. rotundata), bitter (D. dumetorum), Chinese (D. oppositifolia) and water yam (D. alata) have been modified by acid hydrolysis and the physicochemical, material and tablet formation properties of the starches have been investigated with the aim of determining their relative usefulness as a direct compression excipient in pharmaceutical tablets (Odeku and Picker-Freyer, 2009a). The results showed that the acid modified starches differed considerably in their physicocemical and material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Natural D. dumetorum and D. oppositifolia starches were found to be highly compressible and formed tablets of acceptable crushing force while natural D. alata and D. rotundata starches did not form intact tablets except at high compression pressures indicating that the natural forms of D. dumetorum and D. oppositifolia starches could be useful as excipients in tablet formulation by direct compression [6]. These four yam starches when modified by pregelatinization, acid modification, cross-linking, and hydroxypropylation exhibited different properties indicating their potentials for different applications in drug formulation [18][19][20]. The pregelatinized forms of the starches exhibited improved compressibility and flowability than the natural forms of the starches indicating their potential usefulness in direct compression [18,21] while the pregelatinized freeze dried forms of D. dumetorum and D. oppositifolia starches produced tablets which were non-disintegrating the indicating potential application as excipients for controlled drug delivery [18].…”
Section: Yamsmentioning
confidence: 99%
“…The authors concluded that modified D. dumetorum and D. oppositifolia starches could find application as excipients for controlled drug delivery [21]. Furthermore, tablets prepared with acid modified and hydroxypropylated forms of the starches from the Dioscorea species were also shown to exhibit fast disintegration in direct compression indicating that they could be useful as disintegrants in tablet formulations, while others -pregelatinized, freeze-dried, and cross-linked -showed high bond strength with potentials of being useful as binding agents [18][19][20]. The acid modified forms of D. alata and D. rotundata starches have also been shown to possess better disintegrant efficiency than the Natural forms of the starches and corn starch in paracetamol tablet formulations [22].…”
Section: Yamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged mild acid hydrolysis can be performed to produce lintnerized starches. Odeku et al (2009) stated that acid modification has been proven to change the physicochemical properties of starch without destroying its granular structure, yielding starch with increased solubility and gel strength but decreased viscosity. The extent of hydrolysis depends on starch consistency, acidity of the medium, hydrolysis temperature, and duration of hydrolysis.…”
Section: Slow Acid Hydrolysismentioning
confidence: 99%